Concerns about medication and medication adherence in patients with chronic pain recruited from general practice. Issue 2 (22nd November 2011) - Broekmans, Susan; Vanderschueren, Steven
Abstract : Commentary on: Rosser BA McCracken LM Velleman SC . Concerns about medication and medication adherence in patients with chronic pain recruited from general practice. Pain 2011 ;152 :1201 –5 .